2018
DOI: 10.1111/jbfa.12362
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of corporate fraud on director‐interlocked firms: Evidence from bank loans

Abstract: We examine the impact of corporate fraud committed by one firm (the “fraudulent firm”) on other firms with interlocking directors (the “interlocked firms”), focusing on the debtholder side. We argue that the revelation of a fraudulent firm's fraud can damage the reputation of the interlocked firms because corporate governance can propagate via director interlocks. Empirically, we find that the interlocked firms' cost of debt is higher and the loan covenants become stricter after the fraud cases of the fraudule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 81 publications
(166 reference statements)
1
16
0
2
Order By: Relevance
“…Besides that, the percentage of happiness and welfare for principals is too excessive when compared to those allocated to happiness and employee welfare (agents) (Lan & Heracleos, 2010). This opinion is supported and in line with research conducted by who reported that the more extensive and broader its size, the bigger the distribution of the proportion of income distribution depends on management and employees (Lai, Lei, & Song, 2019).…”
Section: Resultssupporting
confidence: 66%
“…Besides that, the percentage of happiness and welfare for principals is too excessive when compared to those allocated to happiness and employee welfare (agents) (Lan & Heracleos, 2010). This opinion is supported and in line with research conducted by who reported that the more extensive and broader its size, the bigger the distribution of the proportion of income distribution depends on management and employees (Lai, Lei, & Song, 2019).…”
Section: Resultssupporting
confidence: 66%
“…Prior research examines the different forms in a variety of contexts, revealing both positive and negative effects. For example, reciprocal interlocks increase innovation but also increase the diffusion of aggressive corporate tax policies, the cessation of quarterly earnings guidance, and increase the cost of debt for non‐fraud firms interlocked with fraud firms (Brown, 2011; Cai et al., 2014; Helmers et al., 2017; Lai et al., 2019). We examine one form of nonreciprocal board interlock, that is, CEOs or CFOs of one firm sitting on another firm's board.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…For example, Stuart and Wang (2016) found that more than half of Chinese technology companies intentionally misrepresented their performance. Furthermore, corporate fraud is argued to have a profoundly negative impact on corporate sustainability and national economic growth (Harris, 2008;Lai et al, 2018;Yin et al, 2020;Zhang et al, 2018). Meanwhile, Zaman et al (2020) called for scholars to understand corporate innovation more in terms of corporate social irresponsibility behavior (e.g., fraud).…”
Section: Introductionmentioning
confidence: 99%